PENGARUH JENIS SPUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN HASIL DUA VARITAS SELADA (Lactuca sativa L.) (Effect of Liquid Organic Fertilizer on the Growth and Yield of Two Varieties of Lettuce (Lactuca sativa L.)) - Made Deviani Duaja; . Gusniwati; Zul Fahri Gani; Helmi Salim (Bioplantae, 2012)
This research was conducted at Teaching and Research Farm, Faculty of Agriculture, University of Jambi. The aimed of this research were to determine the effect of different types of liquid organic fertilizers on the growth and yield of two varieties of lettuce. Experimental design used was a Randomized Block Design with eight treatments and three replications. The treatments were Variety Lettuce + without organic liquid fertilizers, Lettuce + Golden Harvest, Lettuce + Grow Quick, Lettuce + Alam Natural, Variety Grand Rapid + without organic liquid fertilizers, Grand Rapid + Golden Harvest, Grand Rapid + Grow Quick, Grand Rapid + Alam Natural.. The result showed that, there were no significant effect of organic liquid fertilizers on the increase in plant height, the increase in number of leaves, but significant effect of the increase in leaf area. Plant fresh weight (yield) of variety Lettuce with liquid organic fertilizer Golden Harvest gave the highest yields.Keywords: Organic, leaf, fertilizers, height.